CRITERIA FOR ERROR CORRECTION - Turg'unboyeva Hilola Numon qizi Superviser: Kenjayeva Muxlisa Baxadirovna (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
This article explores the essential criteria for effective error correction in educational and professional settings. Error correction plays a crucial role in enhancing learners' understanding, skills, and confidence. The key criteria discussed include clarity in feedback, timeliness of correction, relevance to learning goals, and sensitivity to learners' emotions. The article also highlights the importance of consistency, balancing explicit and implicit correction methods, and encouraging self-correction. Additionally, providing examples, incorporating positive reinforcement, and customizing correction to individual learners are emphasized as effective strategies.